2016
DOI: 10.18357/ijcyfs72201615722
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Pilot Study of a Gratitude Practice Program to Increase Gratitude Among Educators: The First Step Towards Exploring the Potential of Gratitude Practice to Increase Work Engagement and Buffer Against and Decrease Burnout

Abstract: Burnout in educational settings is an international issue. Drawing on practitioner experience in Flexi schools for disenfranchised young people and the methods of positive psychology, this paper outlines a gratitude practice program (GPP) as a proposed intervention to address burnout within Flexi schools. The proposed intervention comprises a full-day workshop and 10 weekly group coaching sessions that aim to develop gratitude practice among teachers. The intention of the paper is to consider the GPP's capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Previous research has consistently shown that gratitude practice results in positive emotions and a high level of satisfaction with life [47]. Based on Fredrickson's [6] broaden-and-build theory, it is possible that gratitude enhances work engagement and enables individuals to experience meaningful work by building their work-related and personal resources [69]. For example, gratitude has been shown to broaden-and-build positive emotions, improve interpersonal relationships, and reduce levels of resentment which, in turn, could foster a co-operative and supportive organizational environment [5,14,45,70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has consistently shown that gratitude practice results in positive emotions and a high level of satisfaction with life [47]. Based on Fredrickson's [6] broaden-and-build theory, it is possible that gratitude enhances work engagement and enables individuals to experience meaningful work by building their work-related and personal resources [69]. For example, gratitude has been shown to broaden-and-build positive emotions, improve interpersonal relationships, and reduce levels of resentment which, in turn, could foster a co-operative and supportive organizational environment [5,14,45,70].…”
Section: Discussionmentioning
confidence: 99%
“…For example, gratitude has been shown to broaden-and-build positive emotions, improve interpersonal relationships, and reduce levels of resentment which, in turn, could foster a co-operative and supportive organizational environment [5,14,45,70]. In addition, feelings of gratitude may foster a positive working environment, enhance learning and growth [71], heighten cognitive performance, increase resilience, improve coping skills, decrease the risk of exhaustion, and increase trust and commitment to the organization [11,46,48,69,72].…”
Section: Discussionmentioning
confidence: 99%
“…Positive psychology, a formal branch of psychology established in the late 1990s, is concerned with promoting optimal conditions for individuals, groups, and organisations to thrive and flourish ( Gable and Haidt, 2005 , Wandell, 2016 ). Gratitude, defined as the appreciation of meaningful elements and experiences in one's life, is a key focus of positive psychology and has been studied as both a trait and a state ( Jans-Becken et al, 2020 ; Sansone and Sansone, 2010 ).…”
Section: Introductionmentioning
confidence: 99%